If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -85 = 11x + 167 Reorder the terms: -85 + 2x = 11x + 167 Reorder the terms: -85 + 2x = 167 + 11x Solving -85 + 2x = 167 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -85 + 2x + -11x = 167 + 11x + -11x Combine like terms: 2x + -11x = -9x -85 + -9x = 167 + 11x + -11x Combine like terms: 11x + -11x = 0 -85 + -9x = 167 + 0 -85 + -9x = 167 Add '85' to each side of the equation. -85 + 85 + -9x = 167 + 85 Combine like terms: -85 + 85 = 0 0 + -9x = 167 + 85 -9x = 167 + 85 Combine like terms: 167 + 85 = 252 -9x = 252 Divide each side by '-9'. x = -28 Simplifying x = -28
| x^2-0+45=0 | | A+6a-14=64 | | w^8+17w^4+70= | | 7x+2yz=-3x+1 | | -76-34-16-34= | | 3x-7.6=29.6 | | X+2x+X=90 | | v=20+3u | | x-4forx=6 | | (x+6.5)(x-6.5)=0 | | -x^2+0+45=0 | | 5x-(-6)=46 | | X+2x+2=90 | | 3x-66=11x+134 | | 5x-(-7)=22 | | 30=(-13) | | -x^4+2x^2+35=0 | | 2(z-3)+4(2z-7)= | | 9w-17w=-16 | | 48y^2+120y+75=0 | | -65-(+42)= | | 5b+2b-6=15 | | (2x-1)(8-x)=0 | | 2x-8x-44=100 | | 5(3z-1)-2(z+1)=10(z+1) | | 2a-3a=7-6a+4-11 | | 14x^3-38x^2+44x-15=0 | | x-9=87 | | friends+fake= | | 15n=-15 | | X+38+38=90 | | -73+2x+7x=98 |